2021
DOI: 10.3389/fpubh.2021.767447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Concise Educational Program on COVID-19 Vaccination Attitudes

Abstract: Background: Vaccination has been recognized as a vital step for containing the COVID-19 outbreak. To ensure the success of immunization efforts as a public health containment measure, a high level of public vaccination compliance is essential. Targeted educational programs can be utilized to improve attitudes toward vaccination and improve the public's uptake of protective measures.Methods: In this cross-sectional study, we aimed to evaluate the impact of a concise educational program on perceived knowledge re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“… 80 , 81 Vaccines could help this goal to an extent, and several studies demonstrated the effective use of health education campaigns to design and implement policies to overcome vaccine hesitancy among the parents and adolescents. 2 , 82 , 83 , 84 , 85 However, this study neither investigated if they had an impact on school attendance, nor whether the level of ‘symptomatic’ illness would have led to absence through symptom severity alone. In the current era of testing and isolation guidance, it is possible that many of the cases wouldn't be detected and that children would continue to attend school.…”
Section: Discussionmentioning
confidence: 95%
“… 80 , 81 Vaccines could help this goal to an extent, and several studies demonstrated the effective use of health education campaigns to design and implement policies to overcome vaccine hesitancy among the parents and adolescents. 2 , 82 , 83 , 84 , 85 However, this study neither investigated if they had an impact on school attendance, nor whether the level of ‘symptomatic’ illness would have led to absence through symptom severity alone. In the current era of testing and isolation guidance, it is possible that many of the cases wouldn't be detected and that children would continue to attend school.…”
Section: Discussionmentioning
confidence: 95%
“…Previous reports have also shown that the trust in COVID-19 vaccine increases with the level of education, and a better understanding of the vaccine properties (12)(13)(14)(15). In particular, communication/video tutorials on vaccine properties and herd immunity may reduce vaccine hesitancy (13,14). It is also expected that doctors may be better able to differentiate between information and misinformation due to their medical training.…”
Section: Discussionmentioning
confidence: 96%
“…Among hospital employees, vaccine acceptance was higher among doctors compared to nurses, and also among those having worked for a longer time in the hospital. Previous reports have also shown that the trust in COVID-19 vaccine increases with the level of education, and a better understanding of the vaccine properties (12)(13)(14)(15). In particular, communication/video tutorials on vaccine properties and herd immunity may reduce vaccine hesitancy (13,14).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, other researchers, based on the results of their systematic review and meta-analysis on the intention to receive the Covid-19 vaccine in HCWs, have emphasized the need for education efforts urgently to improve knowledge, attitude and practice to promote vaccination [27]. Previous studies have also confirmed the effectiveness of educational interventions on vaccine hesitancy [28] and attitudes toward COVID-19 vaccination acceptability [29].…”
Section: Discussionmentioning
confidence: 99%